ChemInform Abstract: Sixteen‐Membered Macrolides: Chemical Modifications and Future Applications. Issue 13 (1st April 2014) - Ajito, Keiichi; Miura, Tomoaki; Furuuchi, Takeshi; Tamura, Atsushi
Abstract Review: 127 refs.